Varietal improvement and dissemination by Ksatsart University, the Thai Tapioca Development Institute and the Dept. of Agricultural Extension - Rojanaridpiched, Chareinsuk; Phongvutipraphan, Somporn; Poolsanguan, Piyawuth; Klakhaeng, Kaival I.; Vichukit, Vichan; Sarobol, Ed (International Center for Tropical Agriculture, 1998)
For decades a cassava yield stagnation has been observed in Thailand. In addition, current prices of cassava roots and products are highly fluctuating, as they depend on the European Union market's price of cereals, the subsidy of which will be relaxed and will soon disappear. Since 1992 the Thai government has been implementing a policy of reducing the cultivated area, while maintaining the quality and total production of cassava, by the replacement of the traditional local variety, Rayong 1 , by higher yielding new varieties. The objective of this paper is to describe the varietal improvement of cassava by Kasetsart University (KU), as well as the cooperative multiplication and dissemination of new, improved cultivars to farmers by KU, the Thai Tapioca Development Institute (TTDI) and the Department of Agricultural Extension (DOAE). Two popular cassava cultivars, Kasetsart 50 and Rayong 5, were officially released in 1992 and 1994, respectively. Subsequent breeding efforts at KU have concentrated on the cross between Rayong 5 and Kasetsart 50. The preliminary results shows that several F, clones from the cross had potential dry root yields 10-30% higher than those of the parents. These promising clones have harvest indices and root starch contents similar to those of the parents, but have a significantly higher total biological yield.